Kinerja Komisi Pemilihan Umum Kota Mataram Dalam Meningkatkan Partisipasi Politik Masyarakat Pada Pemilu Presiden 2024 - Elisa Oktriani; Darmansyah Darmansyah; Yudhi Lestanata; Ilham Zitri (Journal Law and Government, 2025)
This study was conducted to determine the performance of the Mataram City General Election Commission in increasing public political participation in the 2024 presidential election. The research method used is qualitative with a qualitative descriptive approach. Data were obtained through interviews, documentation, and theoretical studies. The results of this study indicate that the performance of the Mataram City General Election Commission in increasing public political participation in the 2024 presidential election has 5 aspects, namely the first quality of work, the quality of work of the Mataram City KPU, namely its success in managing logistics, human resources, and election infrastructure, as well as providing effective complaint channels for voters and election observers. Second productivity, the productivity of the Mataram City KPU, namely conducting voter data collection, procurement of logistics, and socialization to the community such as providing an understanding of the stages in the implementation of the election. Third initiative, the initiative of the Mataram City KPU, namely conducting direct voter education in communities and schools, in order to provide understanding to new voters and conduct intensive training for KPPS officers in increasing capacity and professionalism. Fourth cooperation, the Mataram City KPU has collaborated with the Mataram city government in order to ensure logistical and infrastructure support such as the provision of polling stations, security and campaign facilities, as well as cooperation with community organizations (ORMAS) and non-governmental organizations (NGOs) in various activities such as monitoring polling stations, voter education, and campaign supervision. Fifth responsibility, the responsibility of the Mataram City KPU is to submit reports on the implementation of voting and vote counting to the NTB KPU to the RI KPU such as data on the presence of observers and witnesses for election participants at each polling station, as well as reports on the recapitulation of vote counting results such as data on the acquisition of votes for each candidate at the sub-district and city levels.